Efektivitas Intervensi Buteyko Breathing Terhadap Kualitas Tidur Mahasiswa Keperawatan - Abidin, Imam; Nurlianawati, Lia; Puspitasari, Santi (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Poor sleep quality is a common issue among students, negatively impacting their physical health, mental well-being, and academic performance. Buteyko breathing technique is a non-pharmacological method that has the potential to improve sleep quality by normalizing breathing patterns. This study aims to analyze the effect of Buteyko breathing technique on the sleep quality of students. The research employed a pre-experimental design with a one-group pretest-posttest approach, utilizing the Pittsburgh Sleep Quality Index (PSQI) as an instrument. The sample consisted of 30 final-year nursing students with sleep disturbances, selected through purposive sampling. The intervention involved level 1 Buteyko breathing exercises conducted twice daily, in the morning and evening, over one week. Sleep quality was measured using the PSQI, and data analysis was performed using paired t-tests. The results showed that the mean sleep quality score decreased from 13.07 (poor category) before the intervention to 8.47 after the intervention (p = 0.000). The most significant improvement was observed in the sleep duration component, with a mean reduction of 0.9 points. The Buteyko breathing technique effectively improved the students' sleep quality and can be considered a complementary therapy for addressing sleep disturbances to students.